2014
DOI: 10.1186/1471-2407-14-73
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses of BRCA1-defective and triple-negative breast cancer cells and in vitro BRCA1 interactions induced by metallo-intercalator ruthenium(II) complexes containing chloro-substituted phenylazopyridine

Abstract: BackgroundTriple-negative breast cancer (TNBC) is defined by the absence of expression of estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2. Breast cancers with a BRCA1 mutation are also frequently triple-negative. Currently, there is a lack of effective therapies and known specific molecular targets for this aggressive breast cancer subtype. To address this concern, we have explored the cellular responses of BRCA1-defective and triple-negative breast cancer cells, and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 57 publications
7
31
0
Order By: Relevance
“…It has been reported that ruthenium-based agents can be promising anticancer candidates to treat BRCA1-mutant breast cancers, frequently associated with TNBC [121,122]. The BRCA1 gene responds to DNA damage by being involved in cellular pathways for DNA repair, mRNA transcription, cell cycle regulation, and protein ubiquitination [123,124].…”
Section: Other Ruthenium Complexes For the Treatment Of Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that ruthenium-based agents can be promising anticancer candidates to treat BRCA1-mutant breast cancers, frequently associated with TNBC [121,122]. The BRCA1 gene responds to DNA damage by being involved in cellular pathways for DNA repair, mRNA transcription, cell cycle regulation, and protein ubiquitination [123,124].…”
Section: Other Ruthenium Complexes For the Treatment Of Tnbcmentioning
confidence: 99%
“…The role of BRCA1 is also to regulate chemotherapy-induced DNA damage [124]. Ratanaphan et al (2014) reported ruthenium(II) complexes that showed a promising cytotoxicity in a BRCA1 defective TNBC cell line, HCC1937 [121]. Importantly, complex (25) (Figure 10) induced significantly more cytotoxicity in BRCA1 defective-HCC1937 cells (IC 50 = 1.8 ± 0.1 µM) than in the BRCA1 wild-type cell lines MDA-MB-231 (IC 50 = 13.2 ± 0.3 µM) and MCF7 (IC 50 = 8.2 ± 0.1 µM), suggesting that the higher sensitivity of the BRCA1 defective breast cancer cells to (25) might be due to the inability of the dysfunctional BRCA1 to repair ruthenium-induced DNA damage.…”
Section: Other Ruthenium Complexes For the Treatment Of Tnbcmentioning
confidence: 99%
“…However, caspase-3 protein levels did not alter, while its gene expression is increased in all concentrations tested, probably due to shorter incubation times used in the gene expression assays compared to Western blotting assays. [55], which is commonly mutated in TNBC cells. These data suggest that ruthenium complexes can be an alternative to treat triple negative cancers [56].…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…For example, Biancalana et al [57] observed that ruthenium complexes have good cytotoxic activity, with IC 50 values substantially lower than the values obtained with cisplatin on MDA-MB-231 cells. These differences could be due to the fact that they have different mechanisms of action; for example, the activation of p53-dependent or p53-independent checkpoints by cisplatin or ruthenium complexes, respectively [9,52,54,68]. Since platinum-based drugs and NPMBC act on different pathways, NPMBC could be a new therapeutic option for patients with TNBC resistant to platinum-based drugs.…”
Section: Suppression Of Cancer Cell Viability In Association With Thementioning
confidence: 99%
“…However, both cisplatin chemotherapies and its analogs have been shown to have major drawbacks (i.e., intrinsic and acquired chemoresistance, high general toxicity and limited spectrum of activity) [26] which have motivated extensive investigations into alternative metal-based cancer therapies that effectively target both cancer cell proliferation and metastasis. In this sense, we can mention chemotherapy with gold compounds [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]-because they are nontoxic, nonimmunogenic and have good photothermal and optical properties, biocompatibility and stability [40,47,48]-and also with copper [49][50][51], ruthenium [16,[52][53][54][55][56][57][58][59], iron [56,[60][61][62][63][64][65], palladium [50], silver [66,…”
Section: Introductionmentioning
confidence: 99%